Gonadal Transcriptome Analysis of Sex-Related Genes in the Protandrous Yellowfin Seabream (Acanthopagrus latus) - Li, Shizhu; Lin, Genmei; Fang, Wenyu; Huang, Peilin; Gao, Dong; Huang, Jing; Xie, Jingui; Lu, Jianguo (Frontiers in Genetics, 2020)
Yellowfin seabream (Acanthopagrus latus), a protandrous hermaphroditic fish, is a good model for studying the mechanism of sex reversal. However, limited knowledge is known about the genetic information related to reproduction and sex differentiation in this species. Here, we performed de novo transcriptome sequencing analysis of the testis, ovotestis and ovary, to identify sex-related genes in yellowfin seabream. The results assembled 71765 unigenes, in which 16126 and 17560 unigenes were differentially expressed in the ovotestis and ovary compared to the testis, respectively. The most DEG-enriched KEGG and GO pathways were closely associated with the synthesis of sex steroid hormones. Functional analyses identified 55 important sex-related DEGs, including 32 testis-biased DEGs (dmrt1, amh, sox9, etc.), 20 ovary-biased DEGs (cyp19a, foxl2 and wnt4, etc.), and 3 ovotestis-biased DEGs (lhb, dmrt2 and foxh1). Furthermore, the testis-specific expression of dmrt1 and the brain-pituitary-ovary axis expression of foxl2 were characterized, suggesting that they might play important roles in sex differentiation in yellowfin seabream. Our present work provided important molecular basis for elucidating the mechanisms underlying sexual transition and reproduction regulation in yellowfin seabream.